Tribune of the Bulgarian Exarchate: Novini (1890-1898) - Abdula, Sevba (The Balkans Politics, History and Society)
Newspapers and magazines, serving as mass communication tools, have acted as tribune where the issues of the period could be brought to the forefront and debated from the perspective of Bulgarians since the 19th century. The Bulgarian periodicals published in Istanbul before 1878 became platform for discussing national, religious, and political matters. According to Konstantin Velichkov, a poet, writer, diplomat, and statesman who witnessed the period, “[Ö] The ent-husiasm with which current issues and disputes were discussed in public and the press, without any material interest, was a manifestation of a lofty ideal. The energy and courage of the newspapers were fueled by the awareness that the ca-use they pursued was just. If the spirits in Bulgaria seemed so ready everywhere for a general uprising, and if the leaders of this movement saw that the nation was eager to embrace the call, it was largely due to the newspapers of Istanbul. The future historian of this period will attribute great value to the press, pointing to how, during these difficult times, it carried out its duty with determination, selflessness, and patriotism, and will present it as a rare example of such dedica-tion [Ö]” (Veliçkov, 2017: 50).